The Evolution of Performance Measurement, Career Development, and Compensation for Audit Partners in the Context of Public Scrutiny - Bik, Olof; Bouwens, Jan; Knechel, W. Robert; Zou, Yuxia (The Accounting Review, 2026)
ABSTRACT We examine how audit firms changed their policies regarding audit partner performance measurement, career development, and compensation during a period of heightened public scrutiny of audit quality (2007 to 2017). We theorize how implementing policy changes requires a delicate transition in the organizational design and internal processes of the firms and may not effectively translate into their day-to-day practices. Our access to proprietary performance management policies and individual partner performance and compensation data from the eight largest Dutch audit firms allows us to gain an in-depth understanding of the evolution of performance management for audit partners. We find that most of the policy changes have real consequences. For example, audit quality becomes more consequential to career development, whereas profit sharing becomes better linked to quality and long-term performance. We conclude that audit firms appear effectively responsive to public scrutiny, increasingly aligning partner incentives with societal expectations of audit quality.